EVALUATION OF QUALITY MANAGEMENT CONSTRUCTION OF ARCHIVE BUILDING INSTITUTIONS OF SAMARINDA KALIMANTAN EDUCATION QUALITY EDUCATION - SAMAD, INCE MUHAMMAD MALIQUL (KURVA S JURNAL MAHASISWA, 2020)
The number of Construction Work in Indonesia continues to grow and increase where to facilitate various facilities and infrastructure, but the increase in Construction work must be accompanied by an increase in competent experts so that the existing Standardization or Quality Management can be fulfilled properly. In the construction project there is a party that functions to oversee the network of quality fulfillment processes in a project that plays a major role in the process of minimizing errors that will arise, either because of ignorance or mistakes by workers, and various other possibilities. So that a certain standard or standard is achieved. called Quality Management . In this study using the evaluation method checklist or checklist to control the stages of foundation and poorplat work in the LPMP samarinda building.From the evaluation results obtained the list of referrals used by consultants is the assumption of supervisor consultants, the list of referrals used is different from the standards set by SNI-1734-1989-F and the SBW-08 Module There are many stages of work that are not listed in the list of quality application his.